The potential of wildlife to improve the standard of living and food security in rural Africa - van Hoven, Wouter, speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Poaching, unsustainable wildlife utilization practices and the bush meat trade has cleared wildlife out of many of their former natural habitats in Africa. Based on the success of reintroducing wildlife into the Quicama National Park in Angola in cooperation with the local community, all wildlife that have been settled in the wildlife sterile landscape has flourished, multiplied and not one was lost to poaching over the past 12 years. The community is benefitting now from the Park through amongst others employment and the tourist camp is permanently fully booked. Amongst others, the 34 elephants that were airlifted there in family groups have increased to 120. South Africa has experienced a forty fold increase in its wildlife numbers over a period of 50 years due to the private sector and communities taking custodianship of wildlife on private lands. Based on these experiences and successes in starting new nodes of wildlife in Angola, wildlife can be established in other parts of Africa where civil war and over-utilization like in the bush meat trade has wiped wildlife out. The clearest successes in promoting wildlife conservation outside of protected areas in Africa have been achieved where authority to manage and utilize wildlife has been devolved to the landholder level.
The potential of wildlife to improve the economics and food security in rural Africa
The potential of rhino and other wildlife to improve the living standards and food security in rural Africa
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses